The Effect of Chronic Methylphenidate on Executive Function and Working Memory in Drug-Naïve Children with Attention-Deficit Disorder - Seyedtabaei, Roheila; Mohammadi, Seyed Davood; Seyedtabaei, Reza; Tehranidoust, Mehdi (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Background: The main problem in ADHD patients is disinhibition, while ADD patients mostly suffer from slow cognitive speed. Although studies have shown that children with ADHD have deficits in executive function and working memory, and that acute use of Methylphenidate improves these functions, less study has been done on ADD patients. Methods: A four weeks, experimental, clinical trial was conducted with MPH 1 mg/kg/dose. Participants were 20 children aged 6-11 years with diagnosis ADD. Neuropsychological performance was assessed with scales taken from the Cambridge Neuropsychological Test Automated Battery. Results: Methylphenidate improved problems in some aspects of Stocking of Cambridge test including minimum moves, mean subsequent thinking time and in mean moves, between errors, strategy and total error aspects of Spatial Working Memory. It had no effect on Spatial Span and Intra/Extra Dimensional subscales. Conclusions: Studies show that ADHD patients have defect on all executive and working memory tests and acute and not chronic use of Methylphenidate improves their performance. This different effect of chronic Methylphenidate on ADD and ADHD patients is another sign of different brain involvements in these two subgroups. Keywords: Attention Deficit Hyperactivity Disorder, Attention Deficit Disorder, Methylphenidate, Executive Function, Working Memory